Risk Factors of Stunting In Pangkalan Kuras 2 Public Health Center at Pelalawan District, Riau Province - Mayasari Rahmadhani (Science Midwifery, 2021)
WHO states that, in the world there are more than 2 million deaths in children aged 6 years old to 12 years old are directly related to nutrition, especially those caused by stunting and about 1 million deaths due to lack of energy and protein, vitamin A and zinc. In the 2013 Riskesdas, Riau is known to have a prevalence of stunting toddler for 30%, so Riau is still in a problematic condition, especially its public health related to nutrition. This study is a descriptive analytic study with a cross-sectional design. Where the sampling technique is total sampling with 57 people in total, namely all infant aged 5-56 months in the Pangkalan Kuras 2 Public Health Center, Pelalawan District, Riau Province. The results of the data analysis that obtained are the correlation between the maternal last education p =0.813, correlation of Breastfeeding History p=0.039, correlation of Maternal Height History p=0.357, and correlation of Infant Weight History p=0.337. There is no correlation between a low level of maternal education, a low maternal height history and a low birth weight history on the occurrence of stunting. And there is a correlation between non-exclusive breastfeeding to the occurrence of stunting.